2004
DOI: 10.1007/bf03018426
|View full text |Cite
|
Sign up to set email alerts
|

L’administration prophylactique d’ondansétron ne réduit pas l’incidence de prurit induit par le sufentanil intrathécal

Abstract: P Pu ur rp po os se e: : Postoperative itching after intrathecal (IT) narcotics may be a difficult and important problem for both the anesthesiologist and the patient in the postanesthetic care unit. Since some studies have reported success in preventing itching with ondansetron, we designed a prospective, randomized, double-blinded, and controlled study to test whether prophylactic iv ondansetron effectively reduces the incidence of IT sufentanil-induced pruritus.M Me et th ho od ds s: : Thirty-four patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The incidence of pruritus after epidural or intrathecal opiates is a side-effect that occurs with a frequency ranging between 20 and 80% and little preventive treatment is available [32]. The observed rate of pruritus in our patients was within the reported range [33].…”
Section: Discussionsupporting
confidence: 58%
“…The incidence of pruritus after epidural or intrathecal opiates is a side-effect that occurs with a frequency ranging between 20 and 80% and little preventive treatment is available [32]. The observed rate of pruritus in our patients was within the reported range [33].…”
Section: Discussionsupporting
confidence: 58%
“…Administration of ondansetron was performed before neuraxial anesthesia in 4 studies [22][23][24][25] and intraoperatively after neuraxial anesthesia in 2 studies. [26][27][28][29] Placebo or control treatment was the administration of IV normal saline in 5 studies, and no intervention in 1 study.…”
Section: Study Intervention and Pruritus Assessmentmentioning
confidence: 99%
“…29 Intrathecal opioids were administered as part of combined spinal-epidural anesthesia in the 2 studies involving obstetric patients 22,26,27 and as part of spinal injection in 4 studies. [23][24][25]28,29 All patients were blinded to the study intervention. Pruritus was assessed by a blinded investigator in 5 of the 6 studies.…”
Section: Study Intervention and Pruritus Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed that neuraxial opioid-induced pruritus respond to prophylaxis (3,16,17) and treatment (5,18) with ondansetron. Other studies, however, concluded that ondansetron was not effective in this context (19)(20)(21). Ondansetron seems to be more effective in preventing pruritus induced by morphine than other more potent opioids such as fentanyl and sufentanil.…”
Section: Discussionmentioning
confidence: 94%